2016
DOI: 10.1371/journal.pone.0152986
|View full text |Cite
|
Sign up to set email alerts
|

Provider Decisions to Treat Respiratory Illnesses with Antibiotics: Insights from a Randomized Controlled Trial

Abstract: RationaleLower respiratory tract illness (LRTI) frequently causes adult hospitalization and antibiotic overuse. Procalcitonin (PCT) treatment algorithms have been used successfully in Europe to safely reduce antibiotic use for LRTI but have not been adopted in the United States. We recently performed a feasibility study for a randomized clinical trial (RCT) of PCT and viral testing to guide therapy for non-pneumonic LRTI.ObjectiveThe primary objective of the current study was to understand factors influencing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 49 publications
(40 reference statements)
2
10
0
Order By: Relevance
“…Provider attitude survey data from the Branche et al 26] study revealed that clinical signs of bacterial pneumonia drive the decision to continue antibiotics in patients with suspected LRTI. Similar findings were reported in the United States-based ProACT trial, where the adherence rate for pneumonia was 39% compared with 82% adherence in acute bronchitis [27], suggesting that provider belief about the presence of bacterial infection is difficult to modify with a PCT result.…”
Section: Discussionsupporting
confidence: 80%
“…Provider attitude survey data from the Branche et al 26] study revealed that clinical signs of bacterial pneumonia drive the decision to continue antibiotics in patients with suspected LRTI. Similar findings were reported in the United States-based ProACT trial, where the adherence rate for pneumonia was 39% compared with 82% adherence in acute bronchitis [27], suggesting that provider belief about the presence of bacterial infection is difficult to modify with a PCT result.…”
Section: Discussionsupporting
confidence: 80%
“…A question of what factors caused providers to continue antibiotics is raised. In their follow-up analysis of their randomized trial, Branche and colleagues found that while several factors were mentioned by providers as reasons for deviation from their PCT de-escalation protocol including illness severity, fever, abnormal complete blood count, and others, only diagnosis of pneumonia was significantly associated with nonadherence [25]. An important distinction in this case is that viruses are able to cause radiographic changes [26][27][28].…”
Section: Discussionmentioning
confidence: 93%
“…Despite the fact that patients were excluded if they have radiological evidence of pneumonia, sicker patients received ceftriaxone that is commonly used for pneumonia, albeit inappropriately in that indication as well . Clinicians' perceptions of a patient's severity of disease are noted as an important determinant of inappropriate prescribing . Higher CRP values and all the other clinical parameters in the absence of radiological evidence of pneumonia in COPD patients are classified as AECOPD, and therefore, these patients should not be receiving broad‐spectrum antibiotics like ceftriaxone as per the national guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…16 Clinicians' perceptions of a patient's severity of disease are noted as an important determinant of inappropriate prescribing. 17 Higher CRP values and all the other clinical parameters in the absence of radiological evidence of pneumonia in COPD patients are classified as AECOPD, and therefore, these patients should not be receiving broad-spectrum antibiotics like ceftriaxone as per the national guidelines. Several studies have demonstrated that guideline concordant treatment of pneumonia has resulted in reduced in-hospital mortality, improved times to clinical stability and length of stay, [18][19][20] and has led many hospitals to implement bundles of care or flow charts in an attempt to improve guideline compliance.…”
Section: Discussionmentioning
confidence: 99%